2009
DOI: 10.1007/978-1-4020-9173-5_11
|View full text |Cite
|
Sign up to set email alerts
|

Early Nutrition and Later Obesity: Animal Models Provide Insights into Mechanisms

Abstract: Epidemiological evidence suggests that in utero as well as early postnatal life exposure to an imbalanced nutrition are both related to a greater propensity to become obese in later life. Rodent and sheep models of metabolic programming of obesity by early life nutrition include maternal low and high dietary protein and energy or food intake as well as high fat diets. Maternal nutritional imbalance during pregnancy and/or lactation programs energy expenditure, food intake and physical activity in the offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
0
33
0
1
Order By: Relevance
“…In rodents, previous studies showed that alterations in leptin concentrations during the key perinatal periods of hypothalamic development may program selective leptin resistance (17). Neonatal leptin is required to the adequate development of hypothalamic arcuate nucleus and later functioning of hypothalamic circuits that control energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, previous studies showed that alterations in leptin concentrations during the key perinatal periods of hypothalamic development may program selective leptin resistance (17). Neonatal leptin is required to the adequate development of hypothalamic arcuate nucleus and later functioning of hypothalamic circuits that control energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…bacterial complement (Ozanne et al, 2004;Kotz, 2008;Pomp and Mohlke, 2008;Gluckman and Hanson, 2009;Metges, 2009). We also have strong evidence for genetic effects on aspects of eating behaviour in both humans and rodents (Koteja et al, 2003;de Castro, 2004;Rankinen and Bouchard, 2006;de Krom et al, 2009), and emerging evidence that in rodents and humans the propensity for physical activity and aspects of eating behaviour can be genetically related and possibly genetically correlated (Cai et al, 2006;Jonas et al, 2010a;Kumar et al, 2010).…”
Section: Genetic Basis Of Variation In Physical Activity and Related mentioning
confidence: 99%
“…The main models are based in laboratory rodents, specially rats and mice [10,11], because they are relatively inexpensive to maintain, have a sequenced genome and are easily modified by genetic engineering. Thus, there are many studies on the fetal origin of diseases in rodents.…”
Section: Introductionmentioning
confidence: 99%